2019
DOI: 10.1177/1747493019840932
|View full text |Cite
|
Sign up to set email alerts
|

The randomized study of endovascular therapy with versus without intravenous tissue plasminogen activator in acute stroke with ICA and M1 occlusion (SKIP study)

Abstract: Rationale Bridging therapy with endovascular therapy (EVT) and intravenous thrombolysis (IVT) has been reported to improve outcomes for acute stroke patients with large-vessel occlusion in the anterior circulation. While the IVT may increase the reperfusion rate, the risk of hemorrhagic complications increases. Whether EVT without IVT (direct EVT) is equally effective as bridging therapy in acute stroke remains unclear. Aim This randomized study of endovascular therapy with versus without intravenous tissue pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 10 publications
1
20
0
3
Order By: Relevance
“…Last, the SKIP study (UMIN000021488) investigated the non-inferiority of direct EVT compared to a combination of EVT with 0.6 mg/kg intravenous alteplase in a Japanese population [52]. The trial has been completed and during a presentation at the 2020 International Stroke Conference it was reported that while there was no significant difference in the rate of good outcome (mRS 0-2), non-inferiority of direct EVT could not be established [53].…”
Section: Other Trialsmentioning
confidence: 99%
“…Last, the SKIP study (UMIN000021488) investigated the non-inferiority of direct EVT compared to a combination of EVT with 0.6 mg/kg intravenous alteplase in a Japanese population [52]. The trial has been completed and during a presentation at the 2020 International Stroke Conference it was reported that while there was no significant difference in the rate of good outcome (mRS 0-2), non-inferiority of direct EVT could not be established [53].…”
Section: Other Trialsmentioning
confidence: 99%
“…MT in thrombectomy-capable centers. These trials had longer process times than in our study, which may diminish the efficacy of the MT-only approach [27,28].…”
Section: Discussionmentioning
confidence: 74%
“…Our trial provides novel evidence that direct EVT may be an alternative for bridging therapy. As we know, there are five other similar studies, MR CLEAN NO IV (ISRCTN registry ISRCTN80619088), DIRECT SAFE (ClinicalTrials.gov Identifier: NCT03494920), SWIFT DIRECT (ClinicalTrials.gov Identifier: NCT03192332), SKIP, 18 and DIRECT MT, 19 investigating the same issue. We will contact these research groups.…”
Section: Discussionmentioning
confidence: 99%